"They've conspired against us": Understanding the role of social identification and conspiracy beliefs in justification of ingroup collective behavior. (8th July 2018) - Chayinska, Maria; Minescu, Anca
Abstract: The present research investigates conditions under which beliefs in conspiracy theories predict the desire to justify ingroup behavior in the context of intergroup conflict. We propose that within the context of Ukraine's intergroup conflict over the annexation of Crimea, supporters (but not opponents) of the "Euromaidan" social movement are likely to validate protesters' collective actions as just to the extent that they believe that the authorities are engaged in annexation‐related conspiracies. We also examine the moderating role of perceived political corruption in these processes. Using a public opinion survey of 315 Ukrainians, we found support for our hypothesized moderated mediation model—identification with "Euromaidan" increased beliefs in the annexation‐related conspiracy theories, which in turn, increased justification of protesters' actions in the setting of intergroup conflict. However, this mediation was only observed among those supporters of the Euromaidan who perceived political corruption to be at a low or average level.